A concepção de sistema e a formação da teoria geral do direito ambiental brasileiro: da separação entre sujeito e objeto à sugestão de elementos em prol do aperfeiçoamento de princípios e conceitos nucleares - Silva, Jorge Victor Cunha Barretto da (2013)
The existence of a general theory of environmental law is still a relatively unexplored by Brazilian jurists. Although already discuss the existence of an environmental legal system, the characteristics of this system, individuals who compose it, its object and application methods are still little issues faced by the doctrine. The difficulty that the lawyer has to handle the concepts and institutions environmental law reflects the inadequacy of the practical tools , e.g. civil action , class action , injunction environmental impact study prior to impose appropriate parameters is an effective damage prevention ecological , either the repair or restoration of natural losses already studied. A hopelessness tools in environmental protection grows alarmingly, particularly among environmentalists, who no longer believe in the law as a means to contain the impulse developmental ravaging , pollutes and appropriate , in order to reduce the horizon of survival of future generations on the planet earth . In this backdrop, gutter noted that environmental law has very recent formation , precisely compared with study and improvement of the general theory of private law, whose ancient principles , concepts and institutes underwent thorough reflection, by notable jurists , leading the solid ideas about what they mean / represent to the right and to the dynamics of social relations . Therefore, it is more than necessary doctrinal effort on the general theory of law environment, in order to explain the existence of a Legal System Environmental studying their core ideas, such as "" Polution"", "" Caution"", "" Criminal Liability of Corporations"" , so that such logical categories are better fatically identified and legally interpreted, providing coherence to society , regarding the application of the environmental legal body . Face of this, the purpose of the study suggested herein is not to dwell on sectors or divisions that can be established within the environmental law, as the discipline of water, soil , flora or waste . Instead, look to characterize released figures equate problems , formulate solutions relating to the whole area of environmental law - will study a theme common to most of the standards of environmental law or general relations of use / exploitation of ecological assets .